A Revised Code of Ordinances of the City of Tuscaloosa 162, § 380 (1885) - (:unkn) unknown (My University, 1885)
162, § 380; Prohibited carrying concealed a Bowie-knife, any other knife of like kind, dirk, pistol, other fire-arms of like kind. Violators fined not exceeding fifty dollars and possibly sentenced to hard labor not exceeding sixty days.
Keywords: CARRY - CONCEALED